Pemanfaatan karet skrap limbah vulkanisir ban untuk kompon pedal sepeda motor - Nurhajati, Dwi Wahini (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2009)
The utilization of scrap rubber from tyre-retreading industry for footstep compound have been investigated. Pretreatment of rubber scrap with minarex B was done before it was compounded. The footstep compound was designed with various ratio of RSS/pretreated rubber scrap: 100/0; 75/25; 50/50, and 25/75 respectively. The compounds were prepared on a two-rolls mill machine. The compounds were tested for its physical properties such as tensile strength, elongation at break, abrassion resistance, hardness, density, permanent set, and aging, respectively. Test result was compared with physical properties of current commercial footstep. The physical properties of invented footstep compounds were better than current commercial footstep. The footstep compound made by using the RSS and pretreated rubber scrap in ratio of 75/25 performed the best physical properties with 146,48 kg/cm3 tensile strength; 253,36% elongation at break; 58,33 Shore A hardness, 2,91 mm3/kgm abrasion resistance, 1,23 g/cm3 density, 4,69% permanent set, and the change of physical properties after aging at temperature 70oC for 3 x 24 hours were 1,90% tensile strength, 5,02% elongation at break, and 4,04% hardness, respectively. Molding of footstep was done at 150o C, and 150 kg/cm2 for 10 minutes. Organoleptics test showed molded footstep good appearance, good homogeneity during curing, and good flowing compound respectively when it was moulded.Â Keyword: scrap rubber, waste rubber, tyre-retreading industry, footstep compound, RSS = ribbed smoke sheetÂ ABSTRAKTelah dilakukan penelitian pemanfaatan karet skrap limbah vulkanisir ban untuk kompon diberi perlakuan pendahuluan yaitu dicampur dulu dengan plasticizer minarex B. Kompon untuk pedal sepeda motor dirancang dengan variasi perbandingan ribbed smoke sheet RSS/pretreated karet skrap berturut-turut 100/0; 75/25; 50/50 dan 25/75. Kompon pedal dibuat menggunakan mesin two-roll mill. Kompon pedal yang dihasilkan selanjutnya diuji sifat fisisnya meliputi tegangan putus, perpanjangan putus, ketahanan kikis, kekerasan, berat jenis, pampat tetap, perubahan setelah aging terhadap kekerasan, tegangan putus dan perpanjangan putus. Hasil uji pedal dibandingkan dengan hasil uji pedal sepeda motor komersial di pasaran. Sifat fisis kompon pedal hasil penelitian pada umumnya lebih baik daripada sifat fisis terbaik yaitu tegangan putus 146,48 kg/cm2, perpanjangan putus 523,36%, kekerasan 58,33 Shore A, ketahanan kikis 2,91 mm3/kgm, berat jenis 1,23 g/cm3, pampat tetap 4,69%, dan sifat fisis setelah aging pada suhu 70oC selama 3 x 24 jam memiliki perubahan tegangan putus 1,90%, perpanjangan putus 5,02%, dan kekerasan 4,04%. Pencetakan dilakukan pada tekanan 150 kg/cm2 suhu 150oC selama waktu 10 menit. Secara pengamatan visual pedal sepeda motor yang dihasilkan cukup baik, kematangan merata, kompon dapat mengalir dengan baik dalam cetakan.Â Kata Kunci : karet skrap, limbah vulkanisir ban, kompon pedal sepeda motor, RSS = ribbed smoke sheet.